Post-multiple currency strategy: which way Zimbabwe? - Mbetu, Katazo C.; Chikoko, Laurine; Charumbira, Martin (OSSREA Bulletin, 2016)
The paper explores the options that Zimbabwe can adopt in the short-term and long-term post multiple currency era. The methodology adopts a comparative analysis with countries that have previously experienced similar situations. An evaluation of the convergence characteristics of the economies in the trade bloc is also invoked. Multiple currency regime in Zimbabwe is viewed as a symptom hence accelerating reforms, the major problems would eventually be overcome leading to good money chasing away bad money. The way forward on Zimbabwe post multiple currency strategy is the adoption of the Muddling-through-with Accelerating reforms strategy. In conclusion, the paper advocates for macroeconomic policies that complement with the identified currency option.